К проблеме петрогенезиса карбонат-тальковой толщи Кривбасса - Покалюк, В.В.; Яценко, В. Г. (Видавничий дім "Академперіодика" НАН України, 2008)
New evidence of the stratified volcanogenic nature of metaultrabasites of the talcous subsuit of the Early Pre-Cambrian Kryvorizhsky metamorphic series has been obtained. A group of sedimentary volcanicterrigenous rocks (metaaleuropelites) synchronous and closely connected with ultrabasic volcanicity are petrochemically diagnosed. By a degree of enrichment of these meta-aleuropelites with Fe, Mg, Ca, Cr components, they form a progressive series from ordinary low-ferrousmagnesia aluminiferous phyllite of the Skelevatskaya suite to anomalous highferrous-magnesia differences enriched with calcium and chromium approaching ultrabasites of the talcous horizon to a greater or lesser extent.